2016
DOI: 10.1074/jbc.m115.707877
|View full text |Cite
|
Sign up to set email alerts
|

Romk1 Knockout Mice Do Not Produce Bartter Phenotype but Exhibit Impaired K Excretion

Abstract: Romk knock-out mice show a similar phenotype to Bartter syndrome of salt wasting and dehydration due to reduced Na-K2Cl-cotransporter activity. At least three ROMK isoforms have been identified in the kidney; however, unique functions of any of the isoforms in nephron segments are still poorly understood. We have generated a mouse deficient only in Romk1 by selective deletion of the Romk1-specific first exon using an ES cell CreLoxP strategy and examined the renal phenotypes, ion transporter expression, ROMK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(52 reference statements)
0
11
0
1
Order By: Relevance
“…Moreover, high K + intake increases the activity of ROMK1 in the apical membrane of cortical collecting duct cells, to secrete more K + into the urine and maintain K + balance. Experimental data showed a defect in secretion of K + and hyperkalemia in Romk1 −/− mice under high K + diet [28]. The regulation of K + homeostasis by Klotho was examined by Cha et al (2009).…”
Section: The Biological Functions Of Klotho Proteinmentioning
confidence: 99%
“…Moreover, high K + intake increases the activity of ROMK1 in the apical membrane of cortical collecting duct cells, to secrete more K + into the urine and maintain K + balance. Experimental data showed a defect in secretion of K + and hyperkalemia in Romk1 −/− mice under high K + diet [28]. The regulation of K + homeostasis by Klotho was examined by Cha et al (2009).…”
Section: The Biological Functions Of Klotho Proteinmentioning
confidence: 99%
“…al. demonstrated that ROMK1 isoform, which is expressed in the CCD, but not TAL, was required for ROMK trafficking in response to high K intake 47 . This study suggests that the ROMK2 isoform in the TAL is regulated by different signaling pathways than the ROMK1 in the ASDN.…”
Section: Discussionmentioning
confidence: 96%
“…These isoforms differ at their cytoplasmic amino acid terminus and are differentially expressed in the nephron. Although ROMK knockout mice and rats lacking the three isoforms recapitulate the phenotype of type II Bartter's syndrome (Lu et al, 2002;Lorenz et al, 2002;Zhou et al, 2013), unique functions of the ROMK1 isoform have only been recently elucidated (Dong et al, 2016). ROMK1 knockout did not produce the Bartter's phenotype, and there was no functional coupling between ROMK1 and the Na 1 /K 1 /2Cl 2 cotransporter at the TALH.…”
Section: Discussionmentioning
confidence: 96%
“…Three different ROMK isoforms are present in human and rat kidney (Dong et al, 2016). These isoforms differ at their cytoplasmic amino acid terminus and are differentially expressed in the nephron.…”
Section: Discussionmentioning
confidence: 99%